Anopheles stephensi Feeding, Flight Behavior, and Infection With Malaria Parasites are Altered by Ingestion of Serotonin - Briggs, Anna M.; Hambly, Malayna G.; Simão-Gurge, Raquel M.; Garrison, Sarah M.; Khaku, Zainab; Van Susteren, Grace; Lewis, Edwin E.; Riffell, Jeffrey A.; Luckhart, Shirley (Frontiers in Physiology, 2022)
Approximately 3.4 billion people are at risk of malaria, a disease caused by infection with Plasmodium spp. parasites, which are transmitted by Anopheles mosquitoes. Individuals with severe falciparum malaria often exhibit changes in circulating blood levels of biogenic amines, including reduced serotonin or 5-hydroxytryptamine (5-HT), and these changes are associated with disease pathology. In insects, 5-HT functions as an important neurotransmitter for many behaviors and biological functions. In Anopheles stephensi, we show that 5-HT is localized to innervation in the head, thorax, and midgut, suggesting a gut-to-brain signaling axis that could support the effects of ingested 5-HT on mosquito biology and behavioral responses. Given the changes in blood levels of 5-HT associated with severe malaria and the key roles that 5-HT plays in insect neurophysiology, we investigated the impact of ingesting blood with healthy levels of 5-HT (1.5 µM) or malaria-associated levels of 5-HT (0.15 µM) on various aspects of A. stephensi biology. In these studies, we provisioned 5-HT and monitored fecundity, lifespan, flight behavior, and blood feeding of A. stephensi. We also assessed the impact of 5-HT ingestion on infection of A. stephensi with the mouse malaria parasite Plasmodium yoelii yoelii 17XNL and the human malaria parasite Plasmodium falciparum. Our data show that ingestion of 5-HT associated with severe malaria increased mosquito flight velocity and investigation of visual objects in response to host odor (CO2). 5-HT ingestion in blood at levels associated with severe malaria also increased the tendency to take a second blood meal 4 days later in uninfected A. stephensi. In mosquitoes infected with P. y. yoelii 17XNL, feeding tendency was decreased when midgut oocysts were present but increased when sporozoites were present. In addition to these effects, treatment of A. stephensi with 5-HT associated with severe malaria increased infection success with P. y. yoelii 17XNL compared to control, while treatment with healthy levels of 5-HT decreased infection success with P. falciparum. These changes in mosquito behavior and infection success could be used as a basis to manipulate 5-HT signaling in vector mosquitoes for improved control of malaria parasite transmission.